Determinants of Government Financial Reporting Quality: A Systematic Literature Review on the Role of Human Resource Competency - Suryani Suryani; Sri Rahayu; Wirmie Eka Putra; Rita Friyani; Wiwik Tiswiyanti (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the determinants of the quality of government financial reports with a focus on the role of human resource (HR) competency through a systematic literature review. Based on the analysis of 10 selected articles, it was found that HR competency has a variety of influences on the quality of financial reports, ranging from significant positive to insignificant, depending on the context and moderating variables. Several studies have shown that human resource competency has a direct or indirect effect through mediators such as information quality or internal control systems. On the other hand, other studies have revealed that factors such as information technology, accounting systems, and internal control often have a more dominant impact. These findings highlight the importance of a holistic approach that combines improving HR competency with strengthening supporting systems to achieve optimal financial report quality. The implications of this research can be a reference for the government and stakeholders in designing effective HR development and financial governance policies.